Implementation of Hospital Occupational Health and Safety Programs in Indonesia: A Scoping Review - Putri Agustina; Iwan Muhamad Ramdan; Ida Ayu Indira Dwika Lestari (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Hospitals expose employees to various occupational hazards, including biological, chemical, ergonomic, and psychosocial risks. Although Indonesia has regulations such as Minister of Health Regulation No. 66/2016 on Hospital OHS (K3RS) and the 2024 Hospital Accreditation Standards (KMK No. 1596/2024), OHS program implementation remains inconsistent. Understanding their execution is crucial to enhancing worker and patient safety. Objective : This scoping review aims to map existing evidence on the implementation of hospital occupational health and safety programs (K3RS) in Indonesia, focusing on governance, risk management, program domains, monitoring indicators, enablers, and barriers. Research Methods/ Implementation Methods : The review followed the Joanna Briggs Institute (JBI) framework and PRISMA-ScR guidelines. Literature published between 2015 and 2025 was identified from PubMed, Google Scholar, GARUDA, and DOAJ using keywords related to “K3RS,” “hospital,” “implementation,” and “Indonesia.” Eligible studies included empirical research, reports, and policy analyses focusing on K3RS implementation. Data were charted and synthesized thematically. Results : Hospitals expose employees to various occupational hazards, including biological, chemical, ergonomic, and psychosocial risks. Although Indonesia has regulations such as Minister of Health Regulation No. 66/2016 on Hospital OHS (K3RS) and the 2024 Hospital Accreditation Standards (KMK No. 1596/2024), OHS program implementation remains inconsistent. Understanding their execution is crucial to enhancing worker and patient safety. Conclusion/Lesson Learned : Implementation of hospital OHS programs in Indonesia is progressing but uneven. Strengthening governance, standardizing indicators, and embedding risk-based monitoring are essential for achieving safer hospital work environments.